Date labels, food waste and supply chain implications. (29th September 2022) - Rickard, Bradley J; Ho, Shuay-Tsyr; Livat, Florine; Okrent, Abigail M
Abstract: We developed a survey to collect information on consumers' intentions to discard 15 food products when exposed to different date labels. Results show that the use of certain date labels has the capacity to reduce food waste, but the reductions would happen differentially across food groups. When we examine the nutritional implications, we find that a shift from the 'Best by' date label to the 'Best if Used by' date label would increase total household purchases of energy and lead to a disproportional increase in purchases of fats, cholesterol and protein.